Assessment of the Efficacy and Safety of Enhanced Recovery After Surgery (ERAS) Protocols in Patients Undergoing Bariatric Surgery: A Meta-Analysis: ERAS Protocols in Patients Undergoing Bariatric Surgery - Javed, Muhammad Aslam; Iqbal, Munazza; Ahmed, Arslan; Hassan, Muhammad; Farooq, Nadia; Gillani, Muhammad Mohsin (Pakistan Journal of Health Sciences, 2025)
In modern era bariatric surgeries, the use of several tools of the Enhanced Recovery after Surgery (ERAS) protocols are highly accepted and associated with reduced peri-operative rate of complications and robust recovery. Objectives: To evaluate the impact of application of ERAS protocols in bariatric surgeries, with relevance to postoperative recovery period, postsurgical complications, length of hospital stay and cost effectiveness. Methods: Various randomized controlled trials (RCTs), reviews and observational studies implementing ERAS protocols in bariatric surgeries were included in this meta-analysis after performing a comprehensive search over databases up to August 2024. Results: This meta-analysis affirmed that ERAS protocols significantly reduced the post-operative length of hospitalization by an average of 1.5 days, reduced opioid consumption by approximately 30.7%, and also led to a decreased incidence of major complications (mean 4.16%). The readmission rates remained low (mean 4.16%) in the ERAS group, and overall complication rates were also reduced in studies implementing an increased number of ERAS protocol elements. Subgroup analysis revealed that Sleeve Gastrectomy (SG) was associated with shorter recovery period and fewer complications when compared to Roux-en-Y Gastric Bypass (RYGB). Conclusions: It was concluded that this meta-analysis favors the implementation of ERAS principles in improving outcomes in bariatric surgeries, including shorter hospital stays, reduced recovery period, less need of opioid analgesia and increased patient satisfaction.